Adapting Educational Laboratory Management During the COVID-19 Pandemic: A Case Study at UIN Sunan Kalijaga's Faculty of Islamic Education - Lilis Candra Utami; Rinduan Zain (Journal of Islamic Education Management Research, 2023)
Purpose – This study aims to analyze the management of educational laboratory facilities and infrastructure at the Faculty of Islamic Education, UIN Sunan Kalijaga Yogyakarta, during the COVID-19 pandemic. It focuses on understanding the adjustments and challenges in facility management under pandemic conditions, particularly exploring the role of supporting and inhibiting factors. Design/methods/approach – Adopting a qualitative approach as defined by Bogdan and Taylor, this research involves a detailed examination through interviews, observations, and documentation. Key informants include the Head of the Laboratory and staff at the Faculty of Tarbiyah and Teacher Training. The study employs a thorough process of data analysis, involving transcript preparation, coding, grouping, and interpretation, strengthened by method and source triangulation for data validation. Findings – The study reveals significant changes in the planning, procurement, arrangement, use, and disposal of educational infrastructure during the pandemic. It highlights the crucial role of government policies in facilitating these changes and identifies internal human resource limitations as a primary challenge. The pandemic led to shifts in planning and procurement to suit remote learning needs, emphasizing the need for adaptability in educational infrastructure management. Research implications/limitations – The findings contribute to the academic discourse on educational facility management, particularly under crisis conditions. They provide a framework for understanding the dynamic nature of educational infrastructure management and its responsiveness to unprecedented challenges. Practical implications – This research underscores the importance of flexible and adaptive management strategies in educational settings. It offers practical insights for educational administrators and policymakers on managing physical infrastructure effectively during crises like the COVID-19 pandemic. Originality/value – This study uniquely focuses on the management of educational laboratory facilities during a global pandemic, offering new insights into the adaptability and resilience of educational infrastructure in the face of unforeseen challenges. It extends the discourse on facility management beyond traditional contexts, providing a model applicable in various educational settings, both during and beyond pandemic situations.